Does Mesh Augmentation of the Hiatal Repair with Gore Bio-A® Improve Symptomatic Outcomes in Laparoscopic Fundoplication? - M, Christodoulidou; NR, Kosai; R, Rajan; S, Hassan; S, Das; PA, Sutton; J, Varghese (IIUM Medical Journal Malaysia, 2015)
Introduction: Laparoscopic fundoplication is performed for the management of symptomatic hiatus hernias and gastro-oesophageal reflux disease (GORD) refractory to medical therapy. We adopted the use of Gore Bio-A® for selected laparoscopic hiatus hernia repairs in 2011 and with this case series aimed to establish whether mesh augmentation affects symptomatic outcomes. Methods: A retrospective review of prospectively collected data from all laparoscopic fundoplications performed by a single surgeon between October 2011 and January 2013 was performed. Patient specific data were entered into a proforma and analysed using Microsoft ExcelTM. Patient reported outcomes were assessed with a system specific quality of life questionnaire (GORD-HRQL) both pre and post-operatively. Results: Twenty-three patients underwent laparoscopic fundoplication during the study period. Gore Bio-A® re-enforcement of the hiatal repair was used in 14 patients and was the preferred option for those with pre-operative evidence of a large hiatus hernia. Whilst overall there was a statistically significant difference between pre and post-operative scores (21 vs 0, p=<0.0001, Mann-Whitney U test), there was no clear difference observed in pre-operative scores (22 vs 20, p=0.21, Mann-Whitney U test), postoperative scores (0 vs 0, p=0.92, Mann-Whitney U test) or symptom improvement (21 vs 20, p=0.24, MannWhitney U test) between the mesh and non-mesh groups. Conclusions: Augmentation of the hiatal repair with biosynthetic mesh is safe, feasible and may contribute to improved symptomatic outcomes in selected cases with a large hiatus hernia. We suggest a further assessment with a larger randomised sample and long term follow-up for definitive evaluation.